Design study on very large floating structure for floating island - Mohd. Hafiz Mahyuddin, 1987-; Faizul Amri Adnan, supervisor; Fakulti Kejuruteraan Mekanikal (2010)
Project Paper (Sarjana Muda (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2010